2019
DOI: 10.1530/erp-19-0016
|View full text |Cite
|
Sign up to set email alerts
|

Handheld ultrasound to reduce requests for inappropriate echocardiogram (HURRIE)

Abstract: Background Handheld ultrasound could provide sufficient information to satisfy the clinical questions underlying ‘rarely appropriate’ echo requests, but there are limited data about its use as a gatekeeper to standard echocardiography. We sought to determine whether the use of handheld ultrasound could improve the appropriate use of echocardiography. Method A prospective study comparing handheld ultrasound strategy to standard echocardiography for studies deemed rarely appropriate, using a questionnaire base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
1
5
0
1
Order By: Relevance
“…A prior study demonstrated the feasibility using handheld echocardiography as a screening tool for appropriateness. 11 The present study validates the use of a preliminary limited assessment with a handheld ultrasound device in inpatients meeting appropriate use criteria in the COVID-19 population.…”
Section: Discussionsupporting
confidence: 70%
“…A prior study demonstrated the feasibility using handheld echocardiography as a screening tool for appropriateness. 11 The present study validates the use of a preliminary limited assessment with a handheld ultrasound device in inpatients meeting appropriate use criteria in the COVID-19 population.…”
Section: Discussionsupporting
confidence: 70%
“…Ademais seu uso reduz significantemente o tempo da realização do exame e diminui em até 20% a necessidade de uma ecocardiografia padrão (Haji et al, 2019). Em detrimento a estes achados, estudo (Ashrafian et al, 2004) realizado em UTI evidenciou que mais de trinta por cento de alterações cardíacas clinicamente relevantes não foram identificados por meio do ecocardiograma portátil, o que se atribui a menor definição da imagem deste equipamento (2D), em escala de cinza e doppler colorido.…”
Section: Discussionunclassified
“…HHE systems do not have the full functionality of established echocardiogram machines and are typically limited to two-dimensional (2D) and colour Doppler modalities. 4 There will be scenarios where the standard dataset cannot be achieved due to limited echo windows or in the setting of an acutely decompensating patient requiring an urgent intervention. In such cases, the key echocardiogram views will be dictated by the clinical circumstances.…”
Section: Protocol For Hhe Delivered By the Echocardiography Departmentmentioning
confidence: 99%
“…able time. 4,5 It is important to note handheld ultrasound devices, due to their inherent limitations as outlined above, should only be used in clearly defined clinical settings. Education and training are also important considerations to ensure high clinical standards particularly for healthcare professionals who are RH strain describes increased RV afterload.…”
Section: Limitations Of Hhementioning
confidence: 99%
See 1 more Smart Citation